The Death Penalty: A Multi-level Analysis of Public Opinion - Burgason, Kyle A. (American journal of criminal justice, 2014)
Considerable research has examined public opinion of the death penalty using simplistic questions such as, “Do you favor or oppose the death penalty.” Simply categorizing people into favoring or opposing capital punishment does little to address the array of factors and circumstances that are part of every murder. We examine variables concerning the nature of homicides from a set of 40 murder vignettes used to gauge respondents’ level of support for capital punishment in murder cases. The data are structured such that vignette responses are nested within individuals, meaning a multi-level analysis is appropriate. We used HLM to explore how vignette-level or homicide related characteristics influence support for the death penalty, as well as how individual-level characteristics condition these factors. Analyses revealed that individual-level variables were non-significant when analyzed independently; however, cross-level interactions indicated significant individual-level influences on homicide-level characteristics as they relate to respondents’ support for the death penalty.